2011
DOI: 10.4238/vol10-3gmr1198
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of NaCl tolerance in tomato

Abstract: ABSTRACT. We attempted to find the suitable parents for the development of tomato hybrids for high salt soils by exploiting combining ability, gene action and heterosis. Six salt-tolerant and three salt-intolerant genotypes, along with their 18 F1 crosses, were evaluated at seedling stage under 10 and 15 dS/m (NaCl) salinity stress, compared to the control level of salinity. The experiment was laid out based on a two-way complete randomized design factorial arrangement with two replications; data on root and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The chlorophyll content of transgenic leaves was significantly higher than that of WT leaves, suggesting that MsPOD increased the H 2 O 2 tolerance of the transgenic plants. Many genes that are involved in NaCl tolerance have been identified, and breeders have investigated the genetic mechanisms involved (Saeed et al, 2011). We also found that MsPOD is involved in NaCl resistance.…”
Section: Discussionmentioning
confidence: 67%
“…The chlorophyll content of transgenic leaves was significantly higher than that of WT leaves, suggesting that MsPOD increased the H 2 O 2 tolerance of the transgenic plants. Many genes that are involved in NaCl tolerance have been identified, and breeders have investigated the genetic mechanisms involved (Saeed et al, 2011). We also found that MsPOD is involved in NaCl resistance.…”
Section: Discussionmentioning
confidence: 67%
“…This idea was indirectly supported also by our previous phenotypic analyses of this hybrid collection (Shapira et al, 2014 ). So far, over-dominant genes identified in previous studies had a major effect on the hybrid's phenotype (Wallace, 1957 ; Falk, 1961 ; Muller and Falk, 1961 ; Hua et al, 2003 ; Krieger et al, 2010 ; Saeed et al, 2011 ; Li et al, 2013 ). The over-dominant loci we mapped, including AEP3, had a minor effect in the SK1xS1001 background.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies mapped loci contributing to heterosis, identifying over-dominant loci turned out to be a more difficult task. Consequently, there are only a few known cases, mostly in plants, of single genes that confer heterotic effect by an over-dominant interaction between their alleles (Hua et al, 2003 ; Krieger et al, 2010 ; Saeed et al, 2011 ; Li et al, 2013 ). Over-dominant loci are interesting because of the nature of interaction between their alleles that confers a synergistic effect.…”
Section: Introductionmentioning
confidence: 99%
“…This corresponds to adding 10.227 g of NaCl to a liter of nutritive solution. The selection of this NaCl concentration was based on previous tests and the results from Bogoutdinova et al [5], Sanjuan-Lara et al [14], Ávila-Amador et al [37], Wafa'a [41], and Saeed et al [42]. The floating raft system used with this concentration allowed the survival of seedlings for 12 days after the application of treatments used to discriminate tolerant and susceptible genotypes.…”
Section: Salt Tolerance Test In Seedlingsmentioning
confidence: 99%